Pengukuran Total Harmonic Distortion (THD) Tegangan dan Arus di Lingkungan MATLAB - Andika Iskandar Makdunia (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2026)
The daily operational landscape is fundamentally dependent on electrical energy, with the nature of the electrical loads frequently exhibiting varied profiles. A notable aspect of diminished power quality is harmonic distortion, which is characterized by disturbances in the electrical waveforms of both current and voltage. These disturbances are typically engendered by the functioning of non-linear loads, such as lighting devices, computers, and air conditioning units. This pervasive condition has a detrimental impact on the quality of electrical power. It is documented that pronounced resonance disturbances have the capacity to amplify harmonics significantly, potentially by four to ten times under full load conditions. The utilization of harmonic filters represents a principal method for counteracting harmonic interference. This specific study involved the application of simulations, facilitated by the Matlab Simulink software package. The analysis of the simulation outputs revealed that the Total Harmonic Distortion (THD) for current reached an aggregate of 21.06%, while the corresponding THD for voltage was measured at 20.88%. Furthermore, the most substantial Individual Harmonic Distortion (IHD) for current was observed at the fifth harmonic order, amounting to 19.36%, and similarly, for voltage, the highest IHD was also concentrated at the fifth order, registering 20.88%.